The last kingdom. Seven kings must die [videorecording (DVD)] - Hillier, Martha; Dreymon, Alexander, 1983-; Gilby, Harry; Rowley, Mark, 1990-; Fedaravičius, Arnas, 1991-; Clerkin, Cavan; Northcote, James, 1987-; Davidson, Laurie, 1992-; Strang, Pekka, 1977-; Andrasi, Zoltan; Cornwell, Bernard (Universal Pictures Home Entertainment, 2024)
Alexander Dreymon reprises his lead role as the great warrior Uhtred of Bebbanburg, who must ride once more across a fractured kingdom with several of the series' much-loved returning characters, as they battle alongside, and against, new allies and enemies. Following the death of King Edward, a battle for the crown ensues, as rival heirs and invaders compete for power. And when an alliance comes seeking Uhtred's help in their plans, Uhtred faces a choice between those he cares for most and the dream of forming a united England.